The application of postactivation potentiation on sprint performance - Lim, J. J. H.; Kong, P. W. (Journal of Australian Strength and Conditioning, 2013)
The optimal training protocol to maximize strength and power performance in athletes is greatly sought after by athletes, coaches, and strength and conditioning professionals. The use of strength-power potentiating complexes is one such training method to develop explosive strength in athletes (15). This involves muscular contractions of near-maximal loads, prior to performing an explosive movement with similar biomechanical characteristics (7). This training technique takes advantage of post-activation potentiation (PAP) to increase rate of force development (RFD); that would lead to an increase in acceleration and velocity.